Is It Wise to Wait for Ear to Become Dry in Indian Scenario? - Tiwari, Rakesh (Indian J Otolaryngol Head Neck Surg, 2020)
Tympanoplasty is the standard and well-established procedure for closure of tympanic membrane perforations. Tympanoplasty in wet ear is still a topic of debate among ENT surgeons. This study discusses the balance between wait and watch policy and early intervention in wet ear. It also compares the rate of graft uptake and hearing improvement in Type I tympanoplasty in dry and wet ears. This is a hospital based, observational, descriptive and comparative study. Total 246 patients enrolled in the study. Two groups were created with 123 patients in each group. One included dry ears and another included wet ears. All patients had mucosal type of chronic otitis media. They all underwent Type I tympanoplasty. Graft uptake rate and hearing was compared between both groups. The overall success rate (graft uptake) was 91.06% (224). The success rate in dry ear group was 93.50% (115) and in wet ear group it was 88.62% (109). This study concluded that there is no added advantage of drying the ear rather the delay in treatment increases morbidity and drop outs in Indian scenario.